The Effect of Think Talk Write Learning Model on Improving Mathematical Communication Skills and Matemathical Problem Solving in Grade V Elementary School - Untung Ardi Yulianto; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
Think Talk Write cooperative learning model that affects the mathematical communication and mathematical problem solving skills of fifth grade elementary school students. This study aims to analyze the effect of the application of the Think Talk Write learning model on improving mathematical communication skills and mathematical problem solving skills, this study uses a type of quantitative research with a Quasy Ezperimental Design approach with an Onegrup Pretest-Postest design. The population in this study were all fifth grade elementary school students in the Dipanegara Cluster of 10 schools, with a research sample of 31 fifth grade students at SD Negeri 1 Babadan and SD Negeri 2 Babadan. There were 18 fifth grade students from SD Negeri 1 Babadan as the experimental class and 13 fifth grade students from SD Negeri 2 Babadan as the control group. Data collection techniques used observation instruments/analysis of student answers, test instruments and documentation that had passed the validity and reliability tests. Prerequisite tests needed before testing the hypothesis include normality test, homogeneity test, linear test and regression test. The results obtained showed that the Think Talk Write learning model had an effect on math communication skills by 44.6% and on problem solving skills by 5.7%.